Differential molecular interactions of beta-catenin and plakoglobin in adhesion, signaling and cancer. - Ben-Ze'ev, A.; Geiger, B. (Current Opinion in Cell Biology, 1998)
Plakoglobin and beta-catenin are homologous proteins functioning in cell adhesion and transactivation. Their activities are controlled by three types of interactions: those with cadherins in adherens junctions, linking them to the actin cytoskeleton; interactions in the nucleus, where they bind to transcription factors and stimulate gene expression; interactions of free cytoplasmic beta-catenin with axin and adenomatous polyposis coli (APC) protein which target it for degradation. Studies in the past year have demonstrated the complex interplay between these three types of interactions and the different behavior of beta-catenin and plakoglobin in their involvement in morphogenesis and tumorigenesis strongly suggesting that catenins play key roles in adhesion-mediated signaling.